PELAKSANAAN PEMBAGIAN WARISAN DALAM MASYARAKAT ADAT OSING (STUDI DI DESA ADAT KEMIREN KABUPATEN BANYUWANGI) - Achmad Rizqi Syahbana; Komariah; Sofyan Arief (Indonesia Law Reform Journal, 2021)
The implementation of customary inheritance law is still often used by people in Indonesia, as well as for the Osing indigenous people who live in the Kemiren Traditional Village, Banyuwangi Regency. The implementation of inheritance distribution in the area is still guided by the traditions and culture that have been passed down from generation to generation, so that it continues to develop in order to seek justice in the inheritance system of the Osing indigenous people. On this basis, it is necessary to have a legal instrument that can regulate the customary inheritance law of the Osing tribe. This study aims to help answer these problems by knowing the arrangement and implementation of inheritance distribution in the Osing customary community. The method used in this research is sociological juridical. Data collection techniques used in this study were interviews, documentation, and literature study. The result of this research is that the arrangement of inheritance distribution in the Osing customary community applies the Pancer Line and the Kembang Pathways system, with the distribution of two to one for male heirs and female heirs. As for the implementation of the distribution, it is different from the regulation, namely that the distribution of inheritance between male heirs and female heirs is distributed equally, namely one to one. The arrangement for the distribution of inheritance in the Osing customary community has worked well, although in practice there are differences with the prevailing rules, however, the distribution should be adjusted according to the rules so that customary values ​​are maintained in accordance with the characteristics of Osing's customary inheritance law